The role of accounting conservatism in firms' financial decisions - LEE, Jimmy Kiat Bee (Institutional Knowledge at Singapore Management University, 2012)
This paper investigates whether financial reporting conservatism is related to firms’ financial flexibility and their access to capital. If conservatism facilitates monitoring and governance by capital providers, they should be more willing to extend financing and increase firms’ access to capital. However, because conservatism leads to systematic understatement of net worth and weakens the appearance of firms’ balance sheet strength, it could also reduce firms’ access to capital. This study tests these two opposing views of the relationship between conservatism and firms’ financial flexibility. Results indicate that firms with greater reporting conservatism exhibit less flexibility in their corporate liquidity management, in their debt or equity issuance decisions, in the sensitivity of their investments to financing constraints and in their payout policies. Overall, results suggest that although firms enjoy lower debt contracting costs by reporting conservatively, they forgo some flexibility in future access to capital, and this affects their financial decisions.